Pertumbuhan Tanaman Selada (Lactuca sativa L.) SecaraHidroponik Pada Media Pupuk Organik Cair DariKotoran Kambing Dan Kotoran Kelinci - Indrianasari, Yesi, Dra. Suparti M,Si (2016)
Dirt goat and rabbit droppings are types of animal waste utilization is not maximized. If the waste is treated both types can produce a liquid organic fertilizer which can be used in agriculture. The aim of research to determine the effect of liquid organic fertilizer from rabbits goat manure and dirt on the growth of lettuce plants (Lactuca sativa L.) hydroponically. This research was conducted at the Laboratory of Green House Education Sciences, the Faculty of Education, University of Muhammadiyah Surakarta. The method used in this study is an experiment using a completely randomized design (CRD) pattern of the factors are the type of liquid organic fertilizer of goat manure and rabbit droppings three replications. Data were analyzed by quantitative descriptive analysis. The best treatment for high growth stems are P1 (liquid fertilizer goat manure 500 ml) is with an average growth of 1.7 cm for one month. The best treatment for a number of leaves is P2 (liquid fertilizer rabbit droppings 500 ml) is with an average growth of 3 leaves.